Answer:
-5 or 5 depending on how you write the simplified form
Step-by-step explanation:
![\dfrac{27x^2z}{3x^2z^6}=9x^{2-2}z^{1-6}\\\\\boxed{=9z^{-5}=\dfrac{9}{z^5}}](https://tex.z-dn.net/?f=%5Cdfrac%7B27x%5E2z%7D%7B3x%5E2z%5E6%7D%3D9x%5E%7B2-2%7Dz%5E%7B1-6%7D%5C%5C%5C%5C%5Cboxed%7B%3D9z%5E%7B-5%7D%3D%5Cdfrac%7B9%7D%7Bz%5E5%7D%7D)
__
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
1/a^b = a^-b
__
Some folks like their simplified form to contain only positive exponents. Other folks avoid unnecessary fractions. Choose the form that satisfies your grader.
Answer:
choice a
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
Answer:
x = 7, x = -3
Step-by-step explanation:
We can find the zeros by factoring the equation using the zero product property.
x^2-4x-21 = 0
(x-7)(x+3) = 0
<u>x-7 = 0</u>
x = 7
<u>x+3 = 0</u>
x = -3
Zeros are x=7 and x= -3.
Answer:
The expression which is equivalent to –2i(6 – 7i) is; (0 – 2i)(6 – 7i)